A second locus for Aicardi-Goutières syndrome at chromosome 13q14–21. Issue 5 (20th May 2005) - Ali, M; Highet, L J; Lacombe, D; Goizet, C; King, M D; Tacke, U; van der Knaap, M S; Lagae, L; Rittey, C; Brunner, H G; van Bokhoven, H; Hamel, B; et al.
Abstract : Background: Aicardi-Goutières syndrome (AGS) is an autosomal recessive, early onset encephalopathy characterised by calcification of the basal ganglia, chronic cerebrospinal fluid lymphocytosis, and negative serological investigations for common prenatal infections. AGS may result from a perturbation of interferon α metabolism. The disorder is genetically heterogeneous with approximately 50% of families mapping to the first known locus at 3p21 (AGS1). Methods: A genome-wide scan was performed in 10 families with a clinical diagnosis of AGS in whom linkage to AGS1 had been excluded. Higher density genotyping in regions of interest was also undertaken using the 10 mapping pedigrees and seven additional AGS families. Results: Our results demonstrate significant linkage to a second AGS locus (AGS2) at chromosome 13q14–21 with a maximum multipoint heterogeneity logarithm of the odds (LOD) score of 5.75 at D13S768. The AGS2 locus lies within a 4.7 cM region as defined by a 1 LOD-unit support interval. Conclusions: We have identified a second AGS disease locus and at least one further locus. As in a number of other conditions, genetic heterogeneity represents a significant obstacle to gene identification in AGS. The localisation of AGS2 represents an important step in this process.